ADVENTITIOUS SHOOT REGENERATION OF ROUNDLEAF TOOTHCUP-ROTALA ROTUNDIFOLIA [(BUCH-HAM. EX ROXB) KOEHNE] - M. Karatas; M. Aasim; M. Çiftçioğlu (Journal of Animal and Plant Sciences, 2014)
Roundleaf toothcup - Rotala rotundifolia [(Buch-Ham. ex Roxb) Koehne] is an important aquatic, ornamental and medicinal plant of family Lythraceae. Present study was designed to propagate adventitious shoots regeneration from leaf explants cultured on MS medium supplemented with 5 levels of  0.25-2.00 mg/L BA. Maximum shoot regenration frequency (53.33 percent) and mean number of 17.06 shoots per explant was reocrded on MS medium supplemented with 1.0 mg/L BA. Multiple shoots buds were also induced on all culture mediums most of which were either slow to grow or failed  to convert in to shoots. Transfer of explants to 0.20 mg/L GA3 propmoted the shoot regeneration frequecy to 100 percent on MS medium containing 1.00 mg/L BA and increased mean number of shoots (24.0) on MS medium supplemented with 0.25 mg/L BA-0.20 mg/L GA3. The developing shoots rooted in the shoot elongation medium showed positive effects of BA- 0.20 mg/L GA3 combinations. Thereafter, the developing plantlets were acclimatised in water using pH level of 4.0-10 (7 levels). All plants at pH 4.0 developed necrosis and died; whereas, rest of the plants showed variable grpwth at other pH levels. A comparison among the pH treatments suggested slightly acidic to alkaline medium (pH 6-9) was more appropriate for the acclimatisation of in vitro regenerated plants without having negative effects on plant growth and development.
Keywords: Acclimatisation; Adventitous; Aquatic; In vitro; Shoots; Regeneration